The role of cultural background in enhancing communication skills among academic leaders - Kamal, Halah; Abdul Razak, Norizan; Aladdin, Ashinida (Jurnal Cakrawala Pendidikan, 2024)
Academic leaders in the field of English language teaching (ELT) have come to recognise the vital role of culture in ELT. However, the influence of academic leaders' cultural backgrounds on their communicative competence has not been well-researched. This research aims to investigate the cultural factors affecting communicative competence among academic leaders. Semi-structured online interviews were conducted with nine university leaders from different Iraqi universities, with the criteria being academic leaders who have been in service for more than three years. Four theories serve as its framework and direction: the theories of planned behavior, communicative competence, leadership competence, and communication competence. Interviews were transcribed and analysed using thematic analysis, following key factors such as the impact of each academic leader's cultural background on his or her communicative competence. Effective communication skills have been identified as helpful in problem-solving and developing critical skills. The recommendation is to organise training for academic leaders to use English correctly and appropriately to accomplish communication goals.